Seroprevalence of Galactomannan Aspergillus in COVID-19 patients in Jakarta: A challenge in the pandemic commotion - Anna Rozaliyani (Universitas Muhammadiyah Surabaya, 2023)
COVID-19-associated pulmonary aspergillosis (CAPA) is a severe complication of COVID-19 due to Aspergillus infection. However, the clinical manifestation and radiology findings are not typical and require measurement of Aspergillus galactomannan (GM) level to assist in the diagnosis of CAPA. We evaluated the positivity rate of Aspergillus GM level among COVID-19 patients and investigated the correlation between the GM level and the age of patients. This retrospective observational study compiled the GM results from COVID-19 patients’ sera during the early period of the COVID-19 pandemic from March 2020 to December 2021. All samples underwent an ELISA test to measure Aspergillus GM level. There were 96 patients enrolled in this study. The positivity rate was 33%, with the highest (56%) percentage of positivity observed in the age group 40-59 in the positive Aspergillus GM group. The measurement of Aspergillus GM level among COVID-19 patients with risk factors of CAPA is critical to establish CAPA diagnosis. The availability of Aspergillus GM test in Indonesia is still limited and this issue needs to be addressed by all healthcare experts and stakeholders.